The Effect of Investment and Non-Monotonic of Managerial Ownership on Corporate Value - Lihard Stevanus Lumapow (International Journal of Applied Business and International Management, 2019)
The purpose of this study is to test the investment variable on corporate value. Next will examine the effect non-monotonic of managerial ownership on corporate value. The sample used in this study is a consumer goods industry sector company in the Indonesia Stock Exchange for 5 years (2012-2016). Data collection through time series and cross sectional. Sampling uses purposive sampling technique. The analytical tool used in this study is panel data regression. Based on the hausman test, the suitable approach in this study is random effect model (REM). The results of the research obtained indicate that the investment variable has a negative coefficient but is not significant for the corporate value variable. At the level of low managerial ownership is obtained positive and significant to the value of the company, while managerial ownership at a high level or managerial ownership squared shows a negative coefficient on corporate value but not significant. These results indicate that managerial ownership variables have a non-monotonic effect on corporate value.